2023
DOI: 10.3390/app13084780
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Radiographic Radiolucencies Associated with Class II Composite Restorations

Abstract: Bitewing radiographic examination of the Class II composite restorations is commonly performed for diagnosis and preoperative planning of posterior teeth. The purpose of this study was to describe the prevalence; location; and characteristics of radiolucency findings associated with proximal class II composite restorations. Bitewing radiographs of proximal composite restorations of healthy adult patients (18 to 88 years old) who underwent restorative care at predoctoral clinics at the University of Maryland Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
3
1
0
Order By: Relevance
“…Our findings aligned with previous reports indicating that class II resin composite restorations were highly associated with atypical findings ( AlOtaibi et al, 2020 , Bazerbashi et al, 2023 , de Moura et al, 2011 ). A study conducted in the United States reported that 83.50% of proximal restorations were associated with procedural errors, with interfacial gaps and internal voids being the most frequent observations ( Bazerbashi et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings aligned with previous reports indicating that class II resin composite restorations were highly associated with atypical findings ( AlOtaibi et al, 2020 , Bazerbashi et al, 2023 , de Moura et al, 2011 ). A study conducted in the United States reported that 83.50% of proximal restorations were associated with procedural errors, with interfacial gaps and internal voids being the most frequent observations ( Bazerbashi et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings aligned with previous reports indicating that class II resin composite restorations were highly associated with atypical findings ( AlOtaibi et al, 2020 , Bazerbashi et al, 2023 , de Moura et al, 2011 ). A study conducted in the United States reported that 83.50% of proximal restorations were associated with procedural errors, with interfacial gaps and internal voids being the most frequent observations ( Bazerbashi et al, 2023 ). Another study conducted in Saudi Arabia reported that 61.75% of the class II resin composite restorations were associated with atypical findings, with overhang and voids being recognized as the most common procedural errors ( AlOtaibi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations